PENERAPAN MODEL PEMBELAJARAN QUANTUM TEACHING PADA MATA PELAJARAN IPA UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS SDN 11 KAMPUNG TERANDAM KECAMATAN KOTO XI TARUSAN - Asnimar Asnimar (JRTI (Jurnal Riset Tindakan Indonesia), 2016)
The successfulness of learning process at school is influenced by several factors. Initial observation result indicates that learning process in SDN 11 Kampung Tarandam Kecamatan Koto XI Tarusan did not run condusively so that students’ score of IPA subject decreased. This research is aimed to improve students’ learning achievement of IPA subject by using learning model Quantum Teaching. Subject of this research are students grade V SDN 11 Kampung Terandam Kecamatan Koto XI Tarusan. This research consist of three cycles. Data of research were obtained from observation result and students’ test result. Data were analyzed quantitatively and qualitatively. Researcher decided the standard of students’ learning achievement as 70. After cycle I, students’ learning achievement was 66. after cycle II, students’ learning achievement was 73. After cycle III, students’ learning achievement was 79. result of research show that implementation of learning model Quantum Teaching on IPA subject can improve students’ learning achievement.